The Effect Of Payment Gateway Mediation On The Influence Of Human Capital On Financial Performance Micro, Small And Medium Enterprises - Ammi Sufyah Al Rizqy; Ayu Lucy Larasaty (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze human capital financial performance in Micro, Small, and Medium Enterprises (MSMEs) with payment gateway as a mediating variable. In this study, human capital is measured based on the skills, knowledge, and experience possessed by MSME entrepreneurs, while financial performance is measured based on profitability and operational efficiency. The results of the study indicate that human capital has a positive influence on the use of payment gateways, which in turn has a positive impact on improving the financial performance of MSMEs. The results of payment gateways are not significant on financial performance. Furthermore, there is an insignificant influence of human capital on the use of payment gateways that do not affect financial performance. These findings provide evidence that increasing human capital in MSMEs through mastery of payment technology can improve operational efficiency and overall financial performance.